DINAMIKA PRAKTIK PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KESADARAN BERAGAMA SISWA SEKOLAH MENENGAH KEJURUAN - Sidi’ Abas Asma’ul Fauziah; Syaikhu Rozi; Justsinta Sindi Alivi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the characteristics of students' religious awareness and to analyze the challenges, adaptation processes, and changes in Islamic Religious Education (IRE) practices in fostering religious awareness among students at SMKN 1 Dlanggu Mojokerto. This study employed a qualitative approach using a case study design. Data were collected through observations, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña model, which includes data condensation, data display, and conclusion drawing. The findings indicate that students' religious awareness is reflected in their understanding of religious teachings, worship practices, internalization of religious values, religious experiences, and participation in religious activities, although the consistency of worship is still influenced by various factors. The study also found that Islamic Religious Education practices face challenges arising from technological developments, environmental factors, and students' characteristics. To address these challenges, teachers adapted their instructional strategies and strengthened the school's religious culture, resulting in more contextual, adaptive, and student-centered learning practices. Therefore, adaptive Islamic Religious Education practices contribute to the sustainable development of students' religious awareness.